Faktor-faktor yang Mempengaruhi Implementasi Pedoman Akuntansi Pesantren - Dewi, Divina Mahardika; Yadiati, Winwin; Sukmadilaga, Citra (Jurnal Maksipreneur, 2023)
Along with the development of pesantren which now has other business units managed by pesantren not only manage the assets of pesantren itself, IAI launched pesantren accounting guidelines. This study examined several factors that influence the implementation of Pesantren Accounting Guidelines. The alleged factors include human resource competence, organizational commitment, and utilization of information technology. The data used is a type of primary data by taking the population of all managers and staff of Pesantren Business Unit working in the accounting and finance department in Bandung. The results of this study stated that the implementation of pesantren accounting guidelines is positively and significantly influenced by human resource competencies, organizational commitments, and the utilization of information technology both partially and simultaneously.